1998
DOI: 10.1136/gut.43.1.123
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of therapeutic irradiation for prostatic carcinoma on anorectal function

Abstract: Aim-The incidence of anorectal symptoms after radiotherapy (RTH) for localised pelvic malignant disease is unclear. In addition, the eVects of pelvic irradiation on both anorectal motility and sensory function are poorly defined. A prospective study was therefore performed on 35 patients (55-82 years of age) with localised prostatic carcinoma before and four to six weeks after RTH to assess its eVects on anorectal function. Methods-Anorectal symptoms were assessed by questionnaire. Anorectal pressures at rest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 23 publications
3
57
0
1
Order By: Relevance
“…The effect size for the maximal thickness of the external anal sphincter was in accordance with this result (effect size 0.14), but the effect size for the thickness of the internal anal sphincter suggests a moderate detrimental effect of RT (effect size −0.72). Similar conclusions were drawn from a prospective cohort study conducted by the same author; no differences were found between pre-and postradiation measures of maximal thickness of the external and internal anal sphincters in men treated for prostate cancer in acute [33] and chronic [34] conditions; however, no effect size could be calculated from available data. Another study by Gervaz et al [31] presented an interesting case study with measures until 4 years post-radiation.…”
Section: Resultssupporting
confidence: 65%
See 4 more Smart Citations
“…The effect size for the maximal thickness of the external anal sphincter was in accordance with this result (effect size 0.14), but the effect size for the thickness of the internal anal sphincter suggests a moderate detrimental effect of RT (effect size −0.72). Similar conclusions were drawn from a prospective cohort study conducted by the same author; no differences were found between pre-and postradiation measures of maximal thickness of the external and internal anal sphincters in men treated for prostate cancer in acute [33] and chronic [34] conditions; however, no effect size could be calculated from available data. Another study by Gervaz et al [31] presented an interesting case study with measures until 4 years post-radiation.…”
Section: Resultssupporting
confidence: 65%
“…Out of the eight articles studying these aspects, only two had excellent methodological quality [32,34]. The latter study showed no change of the maximal thickness of the external and internal anal sphincters of men irradiated for prostate cancer, which is corroborated in two other studies of good methodological quality [30,33]. The former study showed decreased urethral length and increased fibrosis in the levator ani and urogenital diaphragm muscles of men irradiated for prostate cancer.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations